Writing radio ads: there is more to it than meets the ear! - Hertz, Tony (Henry Stewart Talks, 2009)
Practical and entertaining collection of approaches, tips and wisdom, How to write dialogue, monologue, radio movies, sounds and music, How to make radio more creative and less limiting, than traditionally assumed
Archived at 2022/03/17